"The Bridge" and the Veiling of Meaning: Investigating the Possible Linguistic Effects of Scientology's Unique Lexicon. (18th October 2019) - Fischer, Benjamin
Abstract : This article examines the possible effects of the unique terminology of theChurch of Scientology on its members. It connects the concepts of the Sapir-Whorf Hypothesis with experimental data on the linguistic effects of differentword categories and applies them to oft-used terms within the Churchof Scientology. A thematic content analysis of an internal Scientology videoassesses the possible linguistic effects of the Scientological lexicon. The analysisis comprised of quantitative and qualitative elements. Unique words inthe video are cataloged by frequency and then tagged by one or more of sixword categories previously proven to have an associated linguistic effect, andthen qualitatively analyzed in regards to the categories' associated effects. Itwas concluded that key effects were exclusivity, complexity, and ambiguity, with terms veiling meaning, possibly causing an impression of Scientology asarcane and distant. Moreover, it was found that the ambiguity of terms andtheir sense of professionalism may cause Scientologists and non-Scientologistsalike to more easily place faith in the legitimacy of the concepts behindthe words. This shows that the kind of terminology used in Scientology orsimilar groups likely has an effect on perception and/or behavior, and maybetter inform Scientologists on the factors that influence their attitudes. Thepaper opens the gates for deeper studies into the discourse, behaviors, andnature of an enigmatic new religious movement.